Violation of “Fundamental Family Rights”: brief notes on the Santa Bárbara Peasant Community v. Peru case - Novoa Campos, Bruno (2018)
In connection with the decision handed down by the Inter-American Court of Human Rights in Santa Bárbara peasant community v. Peru, the author suggeststhat fundamental family rights may well be violated and proposes a relevant method of study to address them.